2007
DOI: 10.1021/ic062409g
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Cp*MoO2+ in Water and Intramolecular Proton-Transfer Mechanism by Stopped-Flow Kinetics and Density Functional Theory Calculations

Abstract: A stopped-flow study of the Cp*MoO3- protonation at low pH (down to zero) in a mixed H2O-MeOH (80:20) solvent at 25 degrees C allows the simultaneous determination of the first acid dissociation constant of the oxo-dihydroxo complex, [Cp*MoO(OH)2]+ (pKa1 = -0.56), and the rate constant of its isomerization to the more stable dioxo-aqua complex, [Cp*MoO2(H2O)]+ (k-2 = 28 s-1). Variable-temperature (5-25 degrees C) and variable-pressure (10-130 MPa) kinetics studies have yielded the activation parameters for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 63 publications
2
46
0
Order By: Relevance
“…[ 47] In that case, we found that the barrier could be dramatically reduced by the proton relay action of a water molecule, which is the reaction solvent, because this allows a reduced angular distortion. In CHCl 3 , the solvent molecules cannot assure a proton relay mechanism, but the same role may be exerted by additional ROOH molecules, and also by the corresponding ROH co-product, once this has started to form, as shown in Scheme 6.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…[ 47] In that case, we found that the barrier could be dramatically reduced by the proton relay action of a water molecule, which is the reaction solvent, because this allows a reduced angular distortion. In CHCl 3 , the solvent molecules cannot assure a proton relay mechanism, but the same role may be exerted by additional ROOH molecules, and also by the corresponding ROH co-product, once this has started to form, as shown in Scheme 6.…”
Section: Resultsmentioning
confidence: 95%
“…[46] Although the dinuclear compound may exert the same mechanistic function as [Cp*MoO 2 Cl] (the Cl ligand being replaced by the oxidobridged Cp*MoO 3 group), only the cationic complex is likely to exert a catalytic function among the charged species, because the water ligand can dissociate rather easily [47] and the resulting coordination site may be used for the oxidant activation. Useful background information comes from our recent computational study of hydration and proton transfer processes for the [Cp*MoO 2 ] + (aq) system.…”
Section: Cp*moo(oh)a C H T U N G T R E N N U N G (Oor)cl] or [Cp*moo(mentioning
confidence: 99%
See 3 more Smart Citations